Managing collective effervescence: 'Zomsumption' and postemotional fandom. (September 2019) - Cronin, James; Cocker, Hayley L.
Based on an analysis of the YouTuber–fan community, we theorize the 'living dead' nature of collective effervescence under postemotional conditions. We introduce the concept of zomsumption, whereby 'dead' emotions are carefully synthesized, governed and presented as 'living' throughout the communal consumption of a totem. Here, we explore fans' efforts to ensure the stability and longevity of their community through the lifelessness of their emotional behaviour. By forfeiting genuine and unfiltered emotions in favour of their rationalization and governance, fans access the illusory potential for more manageable forms of sociability and totemic worship. This outlook prompts us to reconsider the nature of the relationship between consumption communities and dominant structures of feeling. We suggest that consumption communities should not be presumed liberatory retreats from such structures as, contrarily, some may function as microcosms for reflecting and even incubating the wider postemotional order.